Cobalt cross-linked redox-responsive PEG hydrogels: from viscoelastic liquids to elastic solids - Wegner, Seraphine V.; Schenk, Franziska C.; Witzel, Sina; Spatz, Joachim P. (Macromolecules, 2016)
We describe cobalt cross-linked redox-responsive 4-arm histidine-modified PEG (4A-PEG-His) hydrogels, which can be switched from self-healing viscoelastic liquids to form stable elastic solids through a simple oxidation step from Co2+ to Co3+. The dramatic change in gel properties is quantified in rheological measurements and is associated with the altered ligand exchange rate of the cross-linking cobalt ions. While Co2+ forms kinetically labile coordination bonds with low thermodynamic stability, Co3+ forms kinetically inert and highly stable coordination bonds. Unlike the Co2+ cross-linked hydrogels, the Co3+ cross-linked hydrogels do not dissolve in buffer and swell overtime, where they remain intact longer with increasing gel connectivity, increasing polymer concentration and decreasing temperature. Remarkably, these gels can even resist the strong chelator EDTA and withstand both low and high pH due to the low ligand exchange rates in the primary coordination sphere. Overall, the Co2+/3+ redox pair provides an attractive platform to produce redox-responsive materials with big deviations in mechanical and chemical properties.